# I'm not sure it's true. If I have a mistake, can you fix it...

3 views (last 30 days)
Bilal Ates on 10 Jul 2020
Commented: Bilal Ates on 10 Jul 2020
I'm not sure it's true. If I have a mistake, can you fix it
syms x y z;
f0=-4*z*exp(-x^2*y-z^2)*cos(x^2*y)-10*cos(x^2*y)*y*x^2+4*sin(x^2*y)*x^4*y^2+4*cos(x^2*y)*x^4*y^2-sin(x^2*y);
f1=int(f0,z);
f1=int(f1,y);
f1=int(f1,x);f1=simplify(int(f1,x))
f2=int(f0,z);
f2=int(f2,x);
f2=int(f2,x);
f2=int(f2,x);
f2=simplify(int(f2,y))

Steven Lord on 10 Jul 2020
f0=-4*z*exp(-x^2*y-z^2)*cos(x^2*y)-10*cos(x^2*y)*y*x^2+4*sin(x^2*y)*x^4*y^2+4*cos(x^2*y)*x^4*y^2-sin(x^2*y);
This multiplies the exponential term only by the first cosine term. That doesn't match the problem as written. You're missing a set of parentheses.

Bilal Ates on 10 Jul 2020
Could you complete the lack
Bilal Ates on 10 Jul 2020
f0=-4*z*exp(-x^2*y-z^2)*(cos(x^2*y)-10*cos(x^2*y)*y*x^2+4*sin(x^2*y)*x^4*y^2+4*cos(x^2*y)*x^4*y^2-sin(x^2*y));
is it actually this way?
Bilal Ates on 10 Jul 2020
syms x y z;
f0=-4*z*exp(-x^2*y-z^2)*(cos(x^2*y)-10*cos(x^2*y)*y*x^2+4*sin(x^2*y)*x^4*y^2+4*cos(x^2*y)*x^4*y^2-sin(x^2*y));
f1=int(f0,z);
f1=int(f1,y);
f1=int(f1,x);
f1=simplify(int(f1,x))
f2=int(f0,z);
f2=int(f2,y);
f2=int(f2,x);
f2=simplify(int(f2,y))
f3=int(f0,z);
f3=int(f3,y);
f3=int(f3,x);
f3=simplify(int(f3,z))